2015
DOI: 10.1016/j.clinbiomech.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a novel suturing scheme for grafting load-bearing collagen scaffolds for rotator cuff repair

Abstract: Background Currently, there are no well-established suture protocols to attach fully load-bearing scaffolds which span tendon defects between bone and muscle for repair of critical sized tendon tears. Methods to attach load-bearing tissue repair scaffolds could enable functional repair of tendon injuries. Methods Sixteen rabbit shoulders were dissected (New Zealand white rabbits, 1 yr. old, female) to isolate the humeral-infraspinatus muscle complex. A unique suture technique was developed to allow for a 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Results showed that BMP13 promoted tendon healing, because of its superior biological factor, and reduced the incidence of re-tearing. Hatta et al [25][26][27][28][29] demonstrated that BMP13 provided significantly better biomechanical performance when compared to traditional surgery in multiple double rows using the supraspinatus tendon in nine shoulders per group. In the current study, a greater degree of maximum load and stiffness at 16 weeks in the H-dose group suggested differences that were significantly higher than those of the other two groups.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Results showed that BMP13 promoted tendon healing, because of its superior biological factor, and reduced the incidence of re-tearing. Hatta et al [25][26][27][28][29] demonstrated that BMP13 provided significantly better biomechanical performance when compared to traditional surgery in multiple double rows using the supraspinatus tendon in nine shoulders per group. In the current study, a greater degree of maximum load and stiffness at 16 weeks in the H-dose group suggested differences that were significantly higher than those of the other two groups.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Load-displacement curves were recorded using a closed loop controlled mechanical testing device (Test Resource 800LE3-2, Test Resources Inc., MN, USA) as described previously [25]. Briefly, samples were kept hydrated with wet gauze soaked in 1×PBS prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…(A) Composite multilayer woven and electrospun scaffold [17]. (B) Pin woven scaffold made from novel electrochemically aligned collagen threads [19].…”
Section: Woven Tendon Bridging and Reinforcementmentioning
confidence: 99%